Endometriosis - Zondervan, KT; Becker, CM; Koga, K; Missmer, SA; Taylor, RN; Viganò, P (Springer Nature, 2018)
Endometriosis is a common inflammatory disease characterized by the presence of tissue outside the uterus that resembles endometrium, mainly on pelvic organs and tissues. It affects ~5-10% of women in their reproductive years - translating to 176 million women worldwide - and is associated with pelvic pain and infertility. Diagnosis is reliably established only through surgical visualization with histological verification, although ovarian endometrioma and deep nodular forms of disease can be detected through ultrasonography and MRI. Retrograde menstruation is regarded as an important origin of the endometrial deposits, but other factors are involved, including a favourable endocrine and metabolic environment, epithelial-mesenchymal transition and altered immunity and inflammatory responses in genetically susceptible women. Current treatments are dictated by the primary indication (infertility or pelvic pain) and are limited to surgery and hormonal treatments and analgesics with many adverse effects that rarely provide long-term relief. Endometriosis substantially affects the quality of life of women and their families and imposes costs on society similar to those of other chronic conditions such as type 2 diabetes mellitus, Crohn's disease and rheumatoid arthritis. Future research must focus on understanding the pathogenesis, identifying disease subtypes, developing non-invasive diagnostic methods and targeting non-hormonal treatments that are acceptable to women who wish to conceive.